Uma análise do valor social considerado pelo Comitê de Pronunciamentos Contábeis à luz da teoria tridimensional do direito - Szuster, Flávia Rechtman (2011)
This thesis aimed to identify the social value considered by the Comitê de Pronunciamentos Contábeis (CPC) in issuing their pronouncements: getting closer or moving away from the international accounting standards. Accounting is going through a historical moment, marked by the accounting standards´ convergence and by the creation of a universal language. In the process, each country has a framework which can vary from convergence, where countries maintain their regulatory institutions, to endorsement, where an accounting pronouncements´ translation is made. In Brazil, the process is conducted by CPC, composed by six Brazilian private institutions, each representing a different group of economic agents. The CPC issues a statement, which enters into public hearing for at least 30 days. The new version results from the analysis of the suggestions received. We used in the theses Miguel Reale´s Tridimensional Theory of Law, which consists of the standard, fact and value, which are always present and functionally related and dialectic, and suffer interference of power, which determines the positive values, to be preserved, and the negative values, to be banned. The accounting pronouncements related to General Concepts and Disclosure before and after the public hearing were used, as well as the international standard on which the Brazilian statement is based and the suggestions received by the CPC on those accounting pronouncements. The results indicate a strong association between suggestions that intended to get closer to the international standards and acceptance by the CPC. Moreover, the actors involved in the process accept the fact that Brazilian´s pronouncements are getting closer to international standards and begin to understand that changing the international standard is the way of changing the Brazilian pronouncement.